Termite (Isoptera) diversity in pastures from the northeast of the province Corrientes, Argentina - LAFFONT, ENRIQUE RAFAEL; PORCEL, EDUARDO ADOLFO (Revista Colombiana de Entomología, 2007)
The isopteran diversity was studied in three pastures from the northeast of the province Corrientes under intensive grazing management (grazing paddocks). A protocol for the rapid assessment of termite diversity was used, consisting of transect sampling. In each transect, the percentage of sections where termites were detected varied between 75 and 90%. A total of 74 termite samples was collected, all belonging to the family Termitidae (subfamilies Nasutitermitinae, Termitinae, and Apicotermitinae). The species most frequently collected were Cornitermes cumulans and Anoplotermes sp. 1. Only two species (Neocapritermes opacus and Grigiotermes sp. 1) were common to the three sites. The species richness was similar between two of the habitats, with seven species present, while the value was five species in the third pasture. The microhabitats most frequently colonized by termites were epigeal nests, soil between plant roots and surface soil. The soilfeeding termites (70%) dominated the termite assemblage, represented mainly by the subfamilyApicotermitinae. There was no notable influence of the perturbations caused by grazing activity or the type of management on the termite fauna of the analyzed sites.